Association between Covid-19 and Pulmonary Embolism (AC-19-PE study). Issue 196 (December 2020) - Miró, Òscar; Llorens, Pere; Aguirre, Alfons; Lozano, Laura; Beaune, Sebastien; Roussel, Mélanie; Le Borgne, Pierrick; Chouihed, Tahar; Freund, Yonathan; ,
Highlights: The frequency of PE in COVID patients attending Spanish and French ED is around 0.7% The risk of PE in patients coming to ED is more than 7-fold higher in COVID than in non-COVID population. However, once PE is suspected and CTPA is ordered, the rate of PE diagnosis is similar in COVID and non-COVID patients.